Analisis Peningkatan Pemasaran Usaha Mikro Kecil Menengah melalui Media Sosial Di Tengah Pandemi Covid 19 - Puspitasari, Alif Diah; Nawawi, Choirul Hadi; Nurhadiatin, Shella; Hanif, Ahmaad Vikry (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
The Covid 19 pandemic situation cannot result from long-term economic problems. Even so, the community continues to take advantage of the things around them to generate and generate additional finance. One of the uses referred to is the use of social media as a marketing area. The objectives of this study are (1) Knowing the state of micro and small businesses during the Covid 19 pandemic. (2) Analyzing the increase in the marketing of micro, small and medium enterprises through social media. The research method used is descriptive qualitative by utilizing primary and secondary data. Primary data were obtained from micro, small and medium entrepreneurs in the Kediri karisidenan who used social media as a marketing medium during the Covid 19 pandemic. Secondary data were obtained from scientific journals, ministerial survey data and other supporting survey data. The results of this study were (1) The state of micro, small, and medium enterprises in two situations, namely being hit and increasing. As for the increasing condition of micro, small and medium enterprises, namely businesses that use online social media as a marketing area. (2) The use of social media to support marketing during the Covid 19 pandemic has experienced a significant increase. The conclusion of this study is to increase the marketing of micro, small and medium enterprises by utilizing social media.